Survival after operative repair of acute type A aortic dissection varies according to the presence and type of preoperative malperfusion - Wolfe, Stanley B.; Sundt, Thoralf M.; Isselbacher, Eric M.; Cameron, Duke E.; Trimarchi, Santi; Bekeredjian, Raffi; Leshnower, Bradley; Bavaria, Joseph E.; Brinster, Derek R.; Sultan, Ibrahim; Pai, Chih-Wen; Kachroo, Puja; et al. (The journal of thoracic and cardiovascular surgery, 2024)
OBJECTIVE: Approximately one-quarter of patients with acute type A aortic dissection (TAAD) present with concomitant malperfusion of coronary arteries, mesenteric circulation, lower extremities, kidneys, brain, and/or coma. It is generally accepted that TAAD patients who present with malperfusion experience higher mortality rates than patients without, although how specific malperfusion syndromes, alone or in combination, affect mortality is not well described. - METHODS: The International Registry of Acute Aortic Dissection database was queried for patients who underwent surgical repair of TAAD. Patients were stratified according to the presence/absence of malperfusion at presentation. Multivariable logistic regression was used to evaluate in-hospital mortality according to malperfusion type. Kaplan-Meier estimates were used to estimate 30-day postoperative survival. - RESULTS: Six thousand four hundred thirty-seven patients underwent surgical repair of acute TAAD, of whom 2642 (41%) had 1 or more preoperative malperfusion syndromes. Mesenteric malperfusion (adjusted odds ratio [AOR], 4.84; P < .001) was associated with the highest odds of in-hospital mortality, followed by coma (AOR, 1.88; P = .007), limb ischemia (AOR, 1.73; P = .008), and coronary malperfusion (AOR, 1.51; P = .02). Renal malperfusion (AOR, 1.37; P = .24) and neurologic deficit (AOR, 1.35; P = .28) were not associated with increased in-hospital mortality. In patients who survived to discharge, there was no difference in 1-year postdischarge survival in the malperfusion and no malperfusion cohorts (P = .36). - CONCLUSIONS: Survival during the index admission after TAAD repair varies according to the presence and type of malperfusion syndromes, with mesenteric malperfusion being associated with the highest odds of in-hospital death. Not only the presence of malperfusion but rather specific malperfusion syndromes should be considered when assessing a patient's risk of undergoing TAAD repair.
Online verfügbar: 29. September 2022, Version of Record: 12. Juni 2024
Gesehen am 26.02.2025